(untitled) (REMUNOM, 2024)
The present research has as its theme the (IN) effectiveness of self-composition in the Judicial Center for Conflict Resolution and Citizenship (CEJUSC) of Guaraí-TO, in mediation and conciliation hearings of existing conflicts in the systematization, being considered a technique that intends to enhance the procedural economy through the efficient execution of an agreement, with the purpose of resolving the conflict both in the pre-procedural and judicial phases. Thus, self-composition is a method of conflict resolution in which there is no solution without an agreement between the parties involved. In contrast to judicial and arbitration solutions, in which the judge or arbitrator has the power to make decisions without prejudice to the agreement between the parties. The general objective of this work is to analyze the (in)effectiveness of self-composition as a resource to achieve the realization of fundamental rights and guarantees and analyzing the impasses for self-composition in the Judicial Center for Conflict Resolution and Citizenship (CEJUSC) of Guaraí-TO. Therefore, the present work tried to examine the concept and history of self-composition in Brazil, demonstrating how its species are accentuated in everyday life, explaining the techniques used in self-composition, and analyzing the coherence of the device with the factual realization of the audiences, if correctly meet the demands and principles they aim to guarantee. The mixed methodology covers both quantitative and qualitative research, and promotes strategic release in the present study. Therefore, the study of mediation and conciliation techniques was used through mixed methodology covering both qualitative and quantitative methodology that uses the deductive approach method, using the monographic procedure method and literature review research technique, since specialized legal doctrines, articles and other scientific productions relevant to the understanding of the analyzed topic are sought.